The influence of blockchain technology on exchange safety and costs - Brol, Marcin (Wpływ technologii blockchain na bezpieczeństwo i koszty wymiany, 2020)
The goal of this paper is to show the impact of blockchain technology on transaction costs, as well as to show the factors which increase exchange safety when using the blockchain and to point out the potential problems with this technology. A blockchain is an open source, decentralized database, using the Internet and peer-to-peer architecture to register transactions. The potential of this technology leads to the hypothesis that it may become the equivalent of the invisible hand of traditional market exchange, meaning primarily the autonomy of transactions that use it. Blockchain is a mechanism which allows to enforce the execution of agreed contracts through encryption. The qualities of blockchain technology bring the transactions made with its use closer to the conditions of a perfectly competitive market, especially when it comes to transparency and supply and demand dispersion. This results in the diminished ability to influence the price on both sides of the market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 21-31
Keywords: blockchain; network economy; peer-to-peer; market exchange; transaction costs; gospodarka sieciowa; sieci peer-to-peer; wymiana rynkowa; koszty transakcyjne